1996
DOI: 10.3354/ame011229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial activities by solar radiation in nearshore waters and the Gulf of Mexico

Abstract: The effects of ultraviolet ( U V ) r a d~a t~o n on thymldine and leucine incorporation were evarmned In surface waters from the Gulf of Mexico and Santa Rosa Sound a mesotrophlc estuary In no] thwest Florida USA Whole dnd 0 8 ].[m flltered surface waters were incubated w~t h 3 H -t h y m~~n e and 14C-leucine in IJV transparent containers under natural solar radlatlon Solar radlation was either not filtered (samples exposed to UV-B UV-A and photosynthetically active radlatlon PAR), filtered through Mylar 500D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
3
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 21 publications
12
107
3
1
Order By: Relevance
“…All samples used for DMSP turnover and other rate measurements were collected on casts made in the early morning, 0600-0730 h, a time at which bacterial and phytoplankton populations are minimally affected by exposure to daily ultraviolet radiation (Aas et al 1996). At each station, four depths within the upper 100 m were sampled for rate determinations (see below).…”
Section: Methodsmentioning
confidence: 99%
“…All samples used for DMSP turnover and other rate measurements were collected on casts made in the early morning, 0600-0730 h, a time at which bacterial and phytoplankton populations are minimally affected by exposure to daily ultraviolet radiation (Aas et al 1996). At each station, four depths within the upper 100 m were sampled for rate determinations (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it is frequently proposed that UV-R induces an increase in carbon release by phytoplankton. Aas et al (1996) reported a significant stimulatory effect of PAR and PAR + UV-A on BP associated with an increase in organic carbon release in coastal surface water of the Atlantic Barrier Coral Reef. In the same way, their bioassay experiments showed a significant increase in rates of bacterial secondary production, in the growth rates and cell volumes of bacteria grown in sunlightirradiated water samples (i.e.…”
Section: Effect Of Uv-r On Carbon Release By Phytoplanktonmentioning
confidence: 99%
“…Differences in BP, PPP and DPP among the various light treatments were assessed with the Mann-Whitney U-test. All results are mean ± SD reported at a 0.05 significant level (ns = non significant) of the afternoon can be considered as representative of the highest value, particularly since UV inhibition of BP is cumulative over the course of the solar day (Aas et al 1996, Visser et al 2002. Lastly, short-term measurements of UV-R photoinhibition can be difficult to translate to long-term ecological effects.…”
Section: Limitation Of the Studymentioning
confidence: 99%
“…It appears that the ability to take advantage of dynamic light exposure may depend on the taxonomic composition and size structure of the phytoplankton community, their light history, and their nutritional status (Barbieri et al, 2002;Brunet and Lavaud, 2010;Helbling et al, 2013). Knowledge on the photoresponse of (bacterial) heterotrophic activity is much more limited, but a number of studies suggest that significant PAR-driven stimulation frequently occurs (Morán et al, 2001;Church et al, 2004), as does inhibition due to UVR (Aas et al, 1996;Kaiser and Herndl, 1997). There is mounting evidence that UVR resistance and photostimulation responses vary among bacterial phylogenetic groups (Agogué et al, 2005;Alonso-Sáez et al, 2006;RuizGonzález et al, 2012), which might be related to the occurrence of photoheterotrophic metabolisms in the ocean (Kolber et al, 2000;Béjà et al, 2000;Kirchman and Hanson, 2012) or to their interaction with other light-driven processes (see references in Ruiz-González et al, 2013).…”
Section: Introductionmentioning
confidence: 99%